Influence of different type of inlet pipe on the separation characteristic of double-field coupling demulsification and dewatering device. Issue 11 (24th July 2022) - Qiu, Zhi; Gong, Haifeng; Peng, Ye; Chen, Ling; Yu, Bao; Liao, Zhixiang
ABSTRACT: Achieve high-efficiency dewatering and purification of emulsion is not always feasible using conventional single method. A centrifugal separator embedded in electric field can achieve efficient demulsification and dewatering, and reasonably designing the inlet structure is important to improve the separation performance of the device coupled with electric and centrifugal fields. In this paper, the separation performance of a coupling device with four inlet structures was numerically investigated. Coupled (CFD)-population balance model (PBM) was applied to establish a multiphase flow model considering the coalescence and breakage of droplets. The Reynolds stress model was used to predict turbulent flow. The effects of adjusting the inlet type on flow field and separation efficiency were analyzed, and the structure was optimized. Experimental results are in good agreement with the numerical results. Variations in the inlet structures significantly influenced the oil and water separation process. Compared with three other coupling devices, the involute-type inlet coupling device has smaller pressure drop and lower energy loss; larger tangential velocity as well as larger centrifugal force on droplets to increase droplet size, weak turbulence intensity, and stable flow field for promoting oil–water separation. The involute inlet is more conducive to improve the separation efficiency of the coupling device by about 96.57%.